Prevalence of hemoglobinopatities in pregnant women of the stork project, period from january to june 2019 in the state of Piauí (Research, Society and Development, 2020)
Hemoglobinopathies are the most prevalent genetic diseases in the world, the most common being: Sickle Cell Diseases (SS, SC, SD, SE, SF), variant hemoglobins, and thalassemia. Studies show that about 300,000 children are born each year with these diseases and thousands are with sickle cell anemia which is one of the most severe forms of the disease. In Brazil, approximately 3,500 people are born with sickle cell disease and their high morbidity and mortality has been considered a public health issue, as people's life expectancy is reduced. The objective of the study was to analyze the prevalence of hemoglobinopathies in pregnant women in the first semester of 2019, from the 65 municipalities of the state of Piauí that send samples for exam analysis, from Projeto Cegonha, at the LACEN / PI Piauí Hemoglobinopathies Laboratory. The work was performed through analysis of the tests performed by the HPLC methodology of Bio-Rad / USA® Variant II and D10 equipment, and the Lacen-PI NETLAB data system. For data compilation, the spreadsheet was used in the Microsoft Excel® program. Of the approximately 30 municipalities that sent samples for analysis it was found that 4.6% of pregnant women have hemoglobinopathies. The municipalities with the largest number of cases were Teresina, Oeiras and Bom Jesus, but in other 19 cities were found cases of hemoglobinopathies. These results do not match the overall reality of the state of Piauí due to non-adherence of all municipalities which may result in higher rates that have not yet been found, generating a more worrying epidemiological condition. Research is important for policy discussion. such as the epidemiological condition of these diseases in the state of Piauí, genetic counseling, health education, collaborative and research studies to know the impacts in the state regions and practical impact on the lives of people with  hemoglobinopathies.